2020
DOI: 10.2147/ott.s243533
|View full text |Cite
|
Sign up to set email alerts
|

<p>CircRNA hsa_circ_0087862 Acts as an Oncogene in Non-Small Cell Lung Cancer by Targeting miR-1253/RAB3D Axis</p>

Abstract: Purpose: Circular RNAs (circRNAs) have been found to regulate several human tumors. The present study was to explore the mechanism of hsa_circ_0087862 in regulating nonsmall cell lung cancer (NSCLC). Methods: Totally 102 NSCLC cases were enrolled. NCI-H1359 and A549 cells were transfected. Cells viability, apoptosis, migration and invasion were determined by CCK-8 assay, flow cytometry, scratch test and transwell experiment, respectively. Luciferase reporter gene assay and RNA immunoprecipitation (RIP) assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…CircRNA is a special type of endogenous non-coding RNA (ncRNA) [ 22 ]. circRNA is differentially expressed in various types of malignant tumor, including CRC, with its level of expression being closely related to clinical stage and prognosis [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA is a special type of endogenous non-coding RNA (ncRNA) [ 22 ]. circRNA is differentially expressed in various types of malignant tumor, including CRC, with its level of expression being closely related to clinical stage and prognosis [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, we found that cisplatin downregulated the lncRNA, lnc-PGPEP1L-3, which is predicted to sponge miR-25-5p, a miRNA with high sequence homology to lnc-MRPL39-10, a lncRNA upregulated by phenanthriplatin (Table 2; Supplementary Table S1). These miRNAs are associated with Wnt/β-catenin and TGF-β signaling, e.g., miR-25-5p, -30a-3p, -138-5p, -149-3p, -185-5p, -378j, -608, -650, -708-5p, -1253, -1254 and − 4516 (Table 2) [23][24][25][26][27][28][29][30][31][32][33][34][35]. We also used microarray analysis to identify the most up-and downregulated lncRNAs in IMR90 cells and found a set of lncRNAs up-and downregulated by cisplatin or phenanthriplatin compared to control treatment (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Also, we found that cisplatin downregulated the lncRNA, lnc-PGPEP1L-3, which is predicted to sponge miR-25-5p, a miRNA with high sequence homology to lnc-MRPL39-10, a lncRNA upregulated by phenanthriplatin (Table 3; Supplementary Table S1). These miRNAs are associated with Wnt/β-catenin and TGF-β signaling, e.g., miR-25-5p, -30a-3p, -138-5p, -149-3p, -185-5p, -378j, -608, -650, -708-5p, -1253, -1254 and -4516 (Table 3) [23][24][25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Resultsmentioning
confidence: 99%